﻿Inhibitory effects on HepG2 cell proliferation and induction of cell cycle arrest by Chromolaena odorata leaf extract and fractions - Hanifah Yusuf; Marhami Fahriani; Cut Murzalina; Rumaisa Dhifa Mawaddah (Pensoft Publishers, 2022)
Concern about the side effects of liver cancer treatment has driven studies on anticancer to find compounds from plants that can act as chemotherapy. The anticancer activity of Chromolaena odorata against colorectal cancer, lung cancer, leukemia, cervical cancer, breast cancer, and liver cancer has been proven. However, this plant's mechanism that can inhibit liver cancer cell growth is still undetermined. This study aims to investigate the anticancer activity of C. odorata against HepG2 cells. Extraction of C. odorata leaves was done by maceration method using 80% ethanol and further fractionated. Total flavonoid and major compound of the crude extract were determined by aluminum chloride colorimetric assay and Liquid Chromatography-Mass Spectrometry method. The IC50 and proliferation analysis was performed by MTT assay. Cell cycle was analyzed by using flowcytometry. Total flavonoid of 1.95% and compounds such as 5,7,8,3ʹ,4ʹ-Pentamethoxyflavonone, 1-Carboethoxy-β-carboline, 3-Methylcanthin-2, 6- dion, Canthin-6-one were found in C. odorata. The proliferation of HepG2 was significantly lower after 72 hours of incubation with ½ IC50 of C. odorata fractions. HepG2 cells treated with C. odorata extract and fractions were accumulated in the G0-G1 phase. These results indicated that C. odorata leaves could inhibit the proliferation of HepG2 cells and induce cell cycle arrest.